1989
DOI: 10.1111/j.1432-1033.1989.tb14800.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of multiple amino acid substitutions on the polypeptide backbone of tuna and horse cytochromes c

Abstract: The cytochromes c provide a wide range of natural and mutant homologous proteins which may be used to study structure/function relationships in biological electron-transfer reactions. A description of the cytochrome c structure has been provided by high-resolution X-ray crystallography for the cytochromes from tuna, bonito, rice and yeast (Saccharomyces iso-1). Correlation of these structures with NMR parameters is necessary to confirm the structure of the protein in solution and to permit the routine characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…X-ray crystallographic techniques and NMR studies have revealed that this residue is packed together with Thr9, Leu94 and Ile85 around the heme thioether-2 methyl group in tuna cytochrome c (Takano and Dickerson, 1981;Gao et al, 1989;see Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…X-ray crystallographic techniques and NMR studies have revealed that this residue is packed together with Thr9, Leu94 and Ile85 around the heme thioether-2 methyl group in tuna cytochrome c (Takano and Dickerson, 1981;Gao et al, 1989;see Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Mobility of the side chain of Phe82 in ferricytochrome c is inferred from the fact that both ortho and both meta protons on opposite sides of the phenyl ring have the same chemical shifts (Gao et al, 1989;Moore and Williams, 1980;Boswell et al, 1980). The rotational flip-rate of Phe82 has been estimated to be lo3 s-' (Moore et al, 1982).…”
Section: Probing the Phe82 Environment Of Cytochrome C By Proton N M Rmentioning
confidence: 99%
See 2 more Smart Citations
“…A signals from non-coordinating residues, together with (iii) identification of the latter based on characteristic NOESY, COSY and TOCSY pattern^. '^-'^ On the other hand, the potential of pseudo-contact shifts [point (3) ] has not yet been fully exploited, except in the particular case of haeme proteins, where independent information on the magnetic susceptibility tensor is available." '2 When the magnetic susceptibility tensor is unknown, some success has been obtained only in the case of cobalt-substituted protein^,'^*'^ but again advantage was taken of the presence of strongly contact-shifted signals.…”
Section: Introductionmentioning
confidence: 99%